Deep brain stimulation for obsessive compulsive disorder leads to symptom changes of comorbid irritable bowel syndrome - Mohamed A. Abdelnaim; Mohamed A. Abdelnaim; Tobias Hebel; Verena Lang-Hambauer; Verena Lang-Hambauer; Juergen Schlaier; Juergen Schlaier; Berthold Langguth; Berthold Langguth; Andreas Reissmann (Frontiers in Psychiatry)
IntroductionIrritable bowel syndrome (IBS) is a common condition characterized by abdominal pain and altered bowel habits, affecting around 11% of individuals globally. It is linked to dysregulation of the brain-gut axis, with altered activity and connectivity in various brain regions. IBS patients often have psychiatric comorbidities like anxiety, or obsessive-compulsive disorder (OCD). Deep brain stimulation (DBS) is an established treatment option for severe, therapy-refractory OCD. It has been suggested that DBS for OCD could also have a beneficial effect on accompanying IBS-symptoms.Methods and patientsNine patients with treatment-refractory OCD who underwent DBS in the bed nucleus striae terminalis (BNST) have been included in this study (4 males, 5 females, mean age: 39.1 ± 11.5 years). Patients were examined with the Gastrointestinal Symptom Rating Scale for Irritable Bowel Syndrome (GSRS-IBS) as well as the Yale-Brown Obsessive Compulsive Scale (Y-BOCS) both before the beginning of DBS as well as throughout several follow-up visits for 12 months following the start of DBS.ResultsThree patients displayed clinically relevant levels of IBS-symptoms at baseline (GSRS-IBS scores at or beyond 32). All of those three patients showed a reduction of the GSRS-IBS score at the last follow-up (12-40%). For the other 6 patients, 5 of them showed also a reduction of the GSRS-IBS compared to the score at baseline. The mean score for all patients showed a descriptive trend toward score reduction throughout the study period and until the last follow up visit after 12 months. The mean Y-BOCS decreased from 31.11 at baseline to 16.50 at the last follow-up. Out of the 9 patients, 7 (78%) were considered responders with Y-BOCS scores decreasing between 37% to 74%. Moderate-to-large correlations between both scales could be observed at both the 9-month and the 12-month follow-up visit. However, none of these associations was statistically significant.ConclusionIn this study, we found alleviation of IBS symptoms after DBS of the BNST, along with improvement in OCD symptoms. Future research using larger sample sizes should address whether the reductions are tied to the improvement of OCD symptoms or if DBS exerts positive effects on IBS independently of OCD symptoms.